ENDANGERED LOCAL LANGUAGES: EXAMINING THE SCARCITY OF INDIGENOUS LANGUAGE LITERACY IN MERAUKE - Rawuh Yuda Yuwana; Sri Ananda Pertiwi (Acceleration: Multidisciplinary Research Journal, 2024)
This study examines the scarcity of indigenous language literacy in Merauke and the pressing threat of local language extinction. Utilizing a qualitative approach and case study method, the research identifies primary factors influencing the decline in the use of local languages, including the dominance of the Indonesian language, lack of documentation and teaching materials in native languages, and limited educational policy support for language preservation. Furthermore, globalization and modernization have driven younger generations to prioritize languages perceived as more economically and socially valuable. The findings reveal that without sustained revitalization efforts, local languages in Merauke face an increased risk of extinction. Recommendations include developing language documentation programs, integrating local languages into school curricula, and fostering community awareness and pride in native languages. This research aims to serve as a foundation for more effective language preservation strategies in Merauke.